2014
DOI: 10.1002/2014gl061959
|View full text |Cite
|
Sign up to set email alerts
|

Did stresses from the Cerro Prieto Geothermal Field influence the El Mayor‐Cucapah rupture sequence?

Abstract: The M w 7.2 El Mayor-Cucapah (EMC) earthquake ruptured a complex fault system in northern Baja California that was previously considered inactive. The Cerro Prieto Geothermal Field (CPGF), site of the world's second largest geothermal power plant, is located approximately 15 km to the northeast of the EMC hypocenter. We investigate whether anthropogenic fluid extraction at the CPGF caused a significant perturbation to the stress field in the EMC rupture zone. We use Advanced Land Observing Satellite interferom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 30 publications
4
21
0
Order By: Relevance
“…Sarychikhina et al [] also estimated the total rate of volumetric contraction due to fluid extraction of 1.24 × 10 7 m 3 /yr. Trugman et al [] based on 2006–2009 ALOS data and modeling using Mogi sources estimated the rate of volumetric contraction due to fluid extraction of 9 × 10 6 m 3 /yr.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarychikhina et al [] also estimated the total rate of volumetric contraction due to fluid extraction of 1.24 × 10 7 m 3 /yr. Trugman et al [] based on 2006–2009 ALOS data and modeling using Mogi sources estimated the rate of volumetric contraction due to fluid extraction of 9 × 10 6 m 3 /yr.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum coseismic slip occurred at 2–4 km depth next to the CPGF. Trugman et al [] showed that the Coulomb stressing rate at the earthquake hypocenter due to fluid extraction at the CPGF is comparable to the tectonic loading rate and suggested that the EMC earthquake may have been triggered by the geothermal production. The earthquake was followed by a robust afterslip on the EMC rupture [ Gonzalez‐Ortega et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…The consequent adjustment of the stress field and the volumetric deformation of the geologic formations can reactivate faults located in the surroundings of the reservoir (Trugman et al, 2014), induce seismic events (Lei et al, 2013), produce localized ground ruptures (Li et al, 2000), land subsidence (Fielding et al, 1998;Motagh et al, 2008;Chang et al, 2014), or uplift (Vasco et al, 2010;Teatini et al, 2011). Thus, reservoir management raises serious concerns in terms of human health, safety of structures and infrastructures, economic risks, and environmental and hydrologic impact (Morton et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover large earthquakes concentrate along the major, Imperial and Cerro Prieto faults, while scattered seismicity, (mainly swarms), and deformation are observed in the Pull-apart Cerro Prieto Basin (Lomnitz et al, 1970;Nava and Glowacka, 1994;Suárez-Vidal et al, 2008). Fluid extraction began in the Cerro Prieto Geothermal Field (CPGF) in 1973, and brine injection therein began in 1989; these processes have been influencing deformation, stress, and seismicity of the area (Majer and McEvilly, 1981;Glowacka and Nava, 1996;Fabriol and Munguía, 1997;Glowacka et al, 1999Glowacka et al, , 2005Trugman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%